Hôn & blog - Noël, Alyson (Trẻ, 2009)
Having made a pact to help each other not go unnoticed in their sophomore year, Winter is dismayed at how quickly Sloane forgets her promise when she is noticed by the "cool girls" and vows to take revenge.